The Correlation Between Student's Self-Confidence And Speaking Achievement (A Survey At The First Grade Of English Department Of Muhammadiyah University Of Surakarta) - Khoirunniswah, Agustin (2005)
The objective of the study is determining the correlation between self-confidence and speaking achievement of the second semester of English Department students of Muhammadiyah University of Surakarta. The subject of the research is the second semester English Department students of Muhammadiyah University of Surakarta. There are 428 students that are divided into 16 speaking classes. The writer uses multistage sampling and random sampling in taking the sample and she gets 52 students as the sample. In collecting data she gives the questionnaire to the subject and gets the document of speaking score from the lecturer. The construct validity is used to know the validity of items by using correlation product moment, then to know the reliability, she uses Alpha Cronbach. The correlation product moment is used to analyze the data. Based on the data calculation, it shows that the obtained of rxy is 0,733 when rtable is 0,279 at level of significance 0, 05. If the obtained rxy is bigger than rtable, the obtained rxy is significant. From the result of the correlation product moment, self-confidence gives the effective contribution 53% toward speaking achievement and 46, 3% are from the other factors. So, there is significant correlation between self-confidence and speaking achievement. It means that self-confidence has the important role to speaking achievement. The students who have high self-confidence will have good competence in speaking achievement. The Implication of this research is that speaking lecturers, have to pay attention to theirs student' personality factor because personality factor gives contribution to speaking achievement. The lecturers are hoped to manage the classroom well, make comfortable atmosphere and must be creative in order to make the students more interested and enjoy in learning English.